PENERAPAN METODE MIND MAPPING DALAM MENENTUKAN IDE POKOK DAN MEMBUAT RANGKUMAN TEKS UNTUK MENINGKATKAN HASIL BELAJAR SISWA DI KELAS VI SDN 44 CAKRANEGARA - Nengah Arpurina Reskian; Nur Hasanah; Efendi Harahap (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This classroom action research aims to improve learning outcomes in identifying main ideas and summarizing texts through mind mapping method implementation among sixth-grade students at SDN 44 Cakranegara in the 2024/2025 academic year. Using Kemmis & McTaggart's model integrated with Culturally Responsive Teaching (CRT) approach, the research involved 21 students in two cycles. Initial assessments showed only 32% of students could identify main ideas correctly and 24% could create proper summaries. After implementing mind mapping with CRT approach incorporating local cultural contexts, learning outcomes improved significantly from 48% completion rate in Cycle I (average score 63.8) to 86% in Cycle II (average score 77.1). The research demonstrates that mind mapping effectively enhances critical thinking abilities, reading comprehension, and summarizing skills while promoting active student participation in the learning process. The research reveals that the use of the mind mapping method and the CRT approach effectively improves students' learning outcomes, particularly in enhancing language skills, developing higher-order thinking, and boosting students' motivation to learn in the digital era and Indonesian language education.